Immediate surgical treatment results for lateral ventricle neoplasms of the brain in children and adults - Polishchuk, Mykola Y.; Mehrzi, Mohamed K.; Smolanka, Andriy V. (Ukrainian Neurosurgical Journal, 2017)
Objective. Тo analyze and review the immediate surgical treatment results for a wide histological range of lateral ventricle tumors (TLV) in children and adults. Materials and methods. Single centre retrospective study included 234 patients with TLV treated and managed in the Neurosurgery Institute from 1990 to 2016. There were 104 adults (54 females and 50 males) while the children were 139 (89 males and 50 females). Thorough physical examination using neuroimaging methods was performed in all the patients. One-hundred and twenty-three children (lethality 37.4 %) and 85 adult patients underwent surgical treatment (lethality 14.1 %). Results. Hypertensive syndrome as TLV clinical sign prevailed: in 108 (77.7 %) and 83 (79.8 %) pediatric and adult patients, respectively. One-hundred and twenty three pediatric patients underwent surgery: 77 (62.6 %) were discharged after surgery, 46 (37.4%) patients died. While in the adult group 85 patients were operated; 73 (85.9 %) patients were discharged after surgery, and 12 (14.1%) died. Conclusions. Lateral ventricle tumors are complicated pathology manifesting by hypertensive syndrome, require a differentiated choice of adequate surgical approach, since it is accompanied by a high mortality rate and complications in the early postoperative period, mostly in children.